The changing nature of work - Job strain, job support and sickness absence among care workers and in other occupations in Sweden 1991-2013 - Gunnar Aronsson; Staffan Marklund; Constanze Leineweber; Magnus Helgesson (Elsevier, 2021)
This study examined exposure changes in three psychosocial dimensions - job demands, job control, and social support - and the associations between these dimensions and sickness absence throughout the period 1991-2013. The analyses covered periods of economic ups and downs in Sweden and periods involving major fluctuations in sickness absence. Data on care workers (n = 16,179) and a comparison group of employees in other occupations (n = 82,070) were derived from the biennial Swedish Work Environment Survey and linked to register data on sickness absence. Eight exposure profiles, based on combinations of demands, control, and support, were formed. The proportion of individuals with work profiles involving high demands doubled among care workers (14%-29%) while increasing modestly in the comparison group (17%-21%) 1991-2013. The work profile that isolated high-strain (iso-strain), i.e., high demands, low control, and low social support, was more prevalent among care workers, from 4% in 1991 to 11% in 2013. Individuals with work profiles involving high-demand jobs had the highest number of days on sickness absence during the study period and those with the iso-strain work profile had the highest increase in sickness absence, from 15 days per year during 1993-1994, to 42 days during 2000-2002. Employees with a passive work profile (low job demands and low job control) had the lowest rate and the lowest increase in sickness absence. Individuals with active work profiles, where high demands are supposed to be balanced by high job control, had a rather high increase in sickness days around 2000. A conclusion is that there is a long-term trend towards jobs with high demands. This trend is stronger among care workers than among other occupations. These levels of job demands seem to be at such a level that it is difficult to compensate for with higher job control and social support.